2001
DOI: 10.2134/jeq2001.303760x
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Response to Mushroom Composting Emissions as a Function of Chemical Concentration

Abstract: Odor pollution is a major problem facing mushroom [Agaricus bisporus (Lange) Imbach] compost production. Techniques for quantifying mushroom composting odors are needed to assess the effectiveness of odor control measures. Odor samples were obtained in nalophane bags from 11 mushroom composting sites. Samples were collected 0.2 m downwind from the pre-wetting heaps (aerated or unaerated) of raw composting ingredients (wheat straw, poultry and horse manures, and gypsum) and subsequent Phase I composting windrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…Organic acids have received relatively little attention in compost odour research. Nevertheless, acids have been reported in research on odour from mushroom composting (Noble et al, 2001) and composting of food waste in combinations with other substrates (Gallego et al, 2012; Krzymien et al, 1999; Komilis et al, 2004; Mao et al, 2006; Tsai et al, 2008). None of these authors, however, reported acids to be a major component of odour, and unfortunately they did not report pH or organic acid concentrations in compost samples.…”
Section: Introductionmentioning
confidence: 99%
“…Organic acids have received relatively little attention in compost odour research. Nevertheless, acids have been reported in research on odour from mushroom composting (Noble et al, 2001) and composting of food waste in combinations with other substrates (Gallego et al, 2012; Krzymien et al, 1999; Komilis et al, 2004; Mao et al, 2006; Tsai et al, 2008). None of these authors, however, reported acids to be a major component of odour, and unfortunately they did not report pH or organic acid concentrations in compost samples.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of sub-urbanization and the heightened sensitivity of the general population to environmental issues have focused public attention on these issues (Kelsey and Singletary 1997;Duns et al 2004). Growers have adopted several measures to reduce the environmental impact of mushroom farming, including the practice of forced aeration of Phase I compost contained in bunkers or tunnels (Op den Camp et al 1991;Noble et al 2001) and the development of new uses for SMC (AMI 2005;Davis and Kuhns 2005). However, the issues of offensive odor generation and SMC disposal continue to place severe pressure on mushroom growers.…”
Section: Introductionmentioning
confidence: 99%
“…2002, 2004). In particular, studies on nitrogen metabolism in mushroom compost have focused on ammonia assimilation (Noble et al. 2001; Vane et al.…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia assimilation by micro-organisms is considered to be one of the important steps for the removal of ammonia from manure treatment systems (Nakai et al 1999;Sasaki et al 2002Sasaki et al , 2004. In particular, studies on nitrogen metabolism in mushroom compost have focused on ammonia assimilation (Noble et al 2001;Vane et al 2001;Noble et al 2002), and together with the ammonia assimilatory pathway of Agaricus bisporus, these nitrogen metabolism pathways have been well characterized Schaap et al 1996Schaap et al , 1997. Although many species of micro-organisms are known to assimilate ammonia through glutamine synthesis (Merrick and Edwards 1995;Patriarca et al 2002), details of the distribution and function of ammonia-assimilating micro-organisms in the composting process have not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%